TEXTURE SEGMENTATION OF IMAGES OF WEAR ZONES OF CUTTING TOOLS BY AMPLITUDE RECTIFYING METHOD - Polyakova, Marina; Krylov, Victor; Volkova, Natalia (International Journal of Computing, 2014)
The amplitude rectifying method of the texture segmentation of the image of wear zone of cutting tools with tracks of the fragile destruction is developed. The mathematical model of the image of wear zone of cutting tools with tracks of the fragile destruction as a spectral-statistical model of the texture image with the amplitude modulation of intensity is proposed.